Effects of formulated and commercial liquid fertilizer on growth, yield and nutrients content of tomato (Lycopersicon esculentum Mill.) - Rosidi, Nur Adila (2018)
Increasing agricultural activities produced various types of organic wastes. Inappropriate management of these wastes create environmental problem such as land and water pollutions. Wet anaerobic digestion process was use in this study, to produce liquid organo-mineral fertilizer by mixing grey water (washing machines disposal water) with vegetable wastes. Oven-dried vegetable wastes were mixed with non-treated washing machine disposal water at two different ratios. The mixtures were then arranged in orbital shaker before shook for 0, 8, 16 and 24 hours. Liquid sample was collected at 0, 3, 6, 9, 12, and 15 days of incubation before they can be analyze using standard procedures. Generally, formulated fertilizers contain high K content with alkaline pH (>7). Rapid degradation of organic acids might increase the pH of formulated liquid organo-mineral fertilizers whilst the surface size of the vegetable wastes increased nutrients dissolution. Generally, higher vegetables wastes are needed to increase the nutrients content of formulated liquid organo-mineral fertilizers. Five different combinations of formulated liquid fertilizers with commercial liquid fertilizer (AB fertilizer), were then further evaluated to determine their effects, on tomato growth, yield and nutrient contents of tomato. This study was conducted under controlled condition in a shelter house at Universiti Putra Malaysia, Bintulu Campus Sarawak. The plants were monitored for their growth performance up to seven trusses before they can be harvested and analyze for their nutrient content. Treatments using combination of formulated liquid fertilizers (T2, T3, T4 and T5) significantly increased the concentration of N, P, K, Mg and Na in tomato plant. However, the growth and yield of tomato for T1 was significantly higher compared with other treatments. Yet better fruit nutritional value quality such as protein, fat and fibre are higher when the plants received formulated liquid fertilizers. Moreover, tomato plant that treated with formulated liquid fertilizer has no or less microbial population in the fruits. The effectiveness of formulated fertilizers was reduced due to high concentration of Na and pH. Modification of present formulated fertilizers is needed in order to utilize them as an alternative source for chemical fertilizer.